ETHNOBOTANICAL KNOWLEDGE OF THE MOST COMMONLY USED PLANTS IN THE MANAGEMENT OF GASTROINTESTINAL AILMENTS IN YOBE STATE, NIGERIA. - ABDALLAH, MUHAMMAD SALIHU; mustafa, Muskhazli; Nallappan, Meenakshii A/P; Go, Rusea; Go, Rusea (African Journal of Traditional, Complementary and Alternative Medicines, 2020)
Background: Rural and urban people in Nigeria made use of medicinal plants as their curative measures, based on their ancient belief that propounded the authenticity of these plants in treating ailments. Materials and methods: Data were collected through semi-structured questionnaires across the study area (3senatorial districts),The collected plant species were authenticated and given voucher numbers, and the demographic data was subjected to Chi-square (x2) comparisons using SPSS version 22. Results: The major family among the surveyed plants, were Fabaceae (dominant), followed by Anacardiaceae and Combretaceae. Moreover, out of 97 respondents, 81 were male (83.5%) and 16 were female (16.5%). It was observed that respondents that were 41-50 years were many into practice ( p = 0.13. The majority of the respondents as compared using chi-square across the parameters, were illiterates (p = 0.06), and very few had a formal training or exposed to workshops (p = 0.02), while the majority inherited and utilized herbal medicine practice as their main sources of income (p = 0.04). The fidelity levels ranged as follows: For diarrhea (18.5% -100%), dysentery (11.11- 45%), pile (11.11 – 50%) and, ulcer covered 9.1% -100%. The ailments were in the range of 0.69 – 0.75 factors of informant consensus. Plant species with RFC values of 0.34, 0.27 and 0.21 as well as those with 0.1, were regarded to have the highest RFC values. Conclusion: Information collected were mainly on cases of gastrointestinal ailments and first of its kind on the use of medicinal plants in Yobe State, Nigeria.